Predictors of work satisfaction among SHOs during accident and emergency medicine training. Issue 4 (December 1993) - Heyworth, J; Whitley, T W; Allison, E J; Revicki, D A
Abstract : The purpose of this study was to assess the ability of work-related stress, and other work environment characteristics that might affect stress, to predict work satisfaction among senior house officers (SHOs) during accident and emergency (A&E) training. Questionnaires were returned by 365 SHOs, who indicated their year in training, the number of hours worked per week, the type of training hospital, the number of new A&E attendances per year, the ratios of patients and consultants to SHOs at their training hospitals and their likelihood of specializing in A&E. They also completed inventories measuring work-related stress, task and role clarity, work group functioning and work satisfaction. Scores on the satisfaction scale served as the dependent variable in a multiple regression equation. Using an alpha level of 0.05, a significant relationship was detected between satisfaction and the 10 independent variables (P = 0.0001). Direct relationships between task and role clarity (P = 0.0001) and work group functioning (P = 0.0002) were significant, as were inverse relationships between stress (P = 0.0001) and the number of new attendances (P = 0.0321). Management practices, such as orientation sessions, that define tasks and roles, enhance work group cohesiveness and mitigate against stress, should result in increased satisfaction among SHOs.